Chemotactic peptide-induced changes in neutrophil actin conformation (The Rockefeller University Press, 1984)
The effect of the chemotatic peptide, N- formylmethionylleucylphenylalanine (FMLP), on actin conformation in human neutrophils (PMN) was studied by flow cytometry using fluorescent 7-nitrobenz-2-oxa-1,3-diazole (NBD)-phallacidin to quantitate cellular F-actin content. Uptake of NBD-phallacidin by fixed PMN was saturable and inhibited by fluid phase F-actin but not G-actin. Stimulation of PMN by greater than 1 nM FMLP resulted in a dose-dependent and reversible increase in F-actin in 70-95% of PMN by 30 s. The induced increase in F-actin was blocked by 30 microM cytochalasin B or by a t- BOC peptide that competitively inhibits FMLP binding. Under fluorescence microscopy, NBD-phallacidin stained, unstimulated PMN had faint homogeneous cytoplasmic fluorescence while cells exposed to FMLP for 30 s prior to NBD-phallacidin staining had accentuated subcortical fluorescence. In the continued presence of an initial stimulatory dose of FMLP, PMN could respond with increased F-actin content to the addition of an increased concentration of FMLP. Thus, FMLP binding to PMN induces a rapid transient conversion of unpolymerized actin to subcortical F-actin and repetitive stimulation of F-actin formation can be induced by increasing chemoattractant concentration. The directed movement of PMN in response to chemoattractant gradients may require similar rapid reversible changes in actin conformation.